DO INDIVIDUAL CHARACTERISTICS IMPACT WILLINGNESS TO PAY FOR HALAL FOOD? - Wibawa, Berto Mulia; Bramanti, Geodita Woro; Pranindyasari, Chelsia (Journal of Halal Research, Policy, and Industry, 2022)
Eating halal foods is considered an essential part of Islamic practice, as it is compulsory to be a way to maintain physical and spiritual purity. In addition, Muslims are encouraged to consume halal foods as they are believed to benefit their overall well-being and help them maintain a healthy and balanced diet. This study aims to determine the effect of religiosity, religious commitment, and subjective norms on the willingness to pay for halal food. Equipped with purposive random sampling techniques, an online survey with 150 respondents was used to collect the data. The data obtained were then analyzed using Partial Least Square (PLS). This study's findings demonstrate a significant positive influence between religiosity, subjective norms, and religious commitment on willingness to pay for halal food.